2012
DOI: 10.1089/ars.2011.4451
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Hydrogen Sulfide in the Pathogenesis of Diabetes Mellitus and Its Complications

Abstract: In the final section of the review, future research directions and potential experimental therapeutic approaches around the pharmacological modulation of H(2)S homeostasis in diabetes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
145
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(150 citation statements)
references
References 80 publications
2
145
0
3
Order By: Relevance
“…7C). Finally, given that H 2 S plays multiple protective roles in both the vasculature and the heart, it can be suggested that lower circulating and tissue H 2 S levels may contribute to the pathophysiology of diabetes (28) and strategies aimed at correcting this decline may serve as an effective therapeutic option in the treatment of heart disease in the setting of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7C). Finally, given that H 2 S plays multiple protective roles in both the vasculature and the heart, it can be suggested that lower circulating and tissue H 2 S levels may contribute to the pathophysiology of diabetes (28) and strategies aimed at correcting this decline may serve as an effective therapeutic option in the treatment of heart disease in the setting of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, additional studies found that STZ does not alter the expression of either enzyme in the aorta, liver, kidney, or heart (4,27). Despite this contrasting evidence about the effects of STZ-induced diabetes on the expression of CSE and CBS, there is clear evidence that circulating levels of H 2 S are decreased in animal models of diabetes (12,27,37) and may even contribute to the pathophysiology of diabetes (28). More importantly, lower circulating H 2 S levels have been detected in plasma samples taken from patients with type 2 diabetes mellitus (T2DM) (12,32).…”
mentioning
confidence: 97%
“…This indicates that the signaling and effector pathways downstream from H 2 S are not impaired significantly in experimental models used in the current study. It must be noted that, depending on the experimental conditions and models used, the other H 2 S-producing enzyme systems also have been shown to be affected by diabetes and diabetic complications (8)(9)(10)(11)(12)(13)(14)(15)(65)(66)(67); overviewed in [67]). Thus, it is likely that there is a complex dysregulation of the H 2 S system in diabetes, the nature of which depends on the model used, as well as the stage and severity of the disease.…”
Section: M P a I R M E N T O F T H E 3 -M S T / H 2 S P A T H W A Ymentioning
confidence: 99%
“…Experimental evidences have been published implicating H 2 S overproduction as a causative factor in the pathogenesis of β-cell death in diabetes. 12,13 Some other experiments have suggested H 2 S deficiency due to increased H 2 S consumption by hyperglycemic cells, in the pathogenesis of diabetic endothelial dysfunction, diabetic nephropathy, and cardiomyopathy. 12 There is possibility that the modulation of H 2 S production may be a potential therapeutic strategy for diabetes mellitus.…”
Section: Enhanced Plasma H 2 S Levels Associated With Fasting Blood Gmentioning
confidence: 99%
“…12,13 Some other experiments have suggested H 2 S deficiency due to increased H 2 S consumption by hyperglycemic cells, in the pathogenesis of diabetic endothelial dysfunction, diabetic nephropathy, and cardiomyopathy. 12 There is possibility that the modulation of H 2 S production may be a potential therapeutic strategy for diabetes mellitus. 13 This has led researchers to investigate H 2 S related substances for treatment of diabetes.…”
Section: Enhanced Plasma H 2 S Levels Associated With Fasting Blood Gmentioning
confidence: 99%